Integrating hybrid learning and team-based project in EFL writing class - Wijayatiningsih, Testiana Deni; Muhammad Muhibbi; Dodi Mulyadi; J-Roel B.Semilla (JEES (Journal of English Educators Society), 2023)
This study aimed to describe the integration of hybrid learning and team-based projects in learning to write and to explain the effectiveness of implementing hybrid and team-based projects in improving students' writing performances. This research method was mixed with quantitative analysis using quasi-experiments and questionnaires, while qualitative analysis used observations in writing classes. The instruments applied were writing tests, questionnaires, and observations. The results of this study were feasible to be used and tested in a small-scale class in the third semester of English Education at the Universitas Muhammadiyah Semarang. The average result of the validation is more than four scores, so it is in the excellent category. Meanwhile, the results of the analysis of student perspectives on learning through Team-Based Projects are divided into four, namely; student perspectives and motivation regarding the implementation of hybrid learning, student perspectives on the effectiveness of Team-Based Projects, student perceptions of independent learning through team-based projects and hybrid learning, and student perceptions about working in groups. All of the indicators were categorized as excellent. In addition, the integration of hybrid learning and team-based project in the English Language Education Study Program with the participation of seventy-two students with the final grades of all students being in the complete category above seventy so that the integration of hybrid learning and team-based projects is effectively implemented in genre text writing classes. Therefore, the results of this study can make a good contribution because they can motivate students to write texts and improve independent student learning. HIGHLIGHTS: Integrating hybrid learning and team-based projects is suitable for use and testing in small class scales in the third semester of English Education at the Muhammadiyah University of Semarang. The average result of the validation results is more than 4.00, so it is in the excellent category. The student perspectives on learning through Team-Based Projects are divided into four: student perspectives on motivation and their writing results, student perspectives on the effectiveness of Team-Based Projects, student perceptions of independent learning through Team-Based Projects and Hybrid understanding, and student perceptions about working in groups. The lecturers should apply hybrid learning and team-based projects to motivate and train students to learn independence and provide experiences of a harmonious learning process. Next, for future researchers, it is advisable to expand the research subject so that the results obtained are more in-depth and can be implemented in other English skills, namely speaking, listening, and reading.